Synthesis and Structures of Ruthenium Carbonyl Complexes Bearing Pyridine-Alkoxide Ligands and Their Catalytic Activity in Alcohol Oxidation - Yan, Xinlong; Yue, Xiaohui; Liu, Kang; Hao, Zhiqiang; Han, Zhangang; Lin, Jin (Frontiers in Chemistry, 2019)
Reaction of Ru3(CO)12 with two equiv of 6-bromopyridine alcohols 6-bromopyCHROH [(R = C6H5 (L1); R = 4-CH3C6H4 (L2); R = 4-OMeC6H4(L3); R = 4-ClC6H4 (L4); (R = 4-CF3C6H4 (L5); R = 2-OMeC6H4 (L6); R = 2-CF3C6H4 (L7)] and 6-bromopyC(Me)2OH (L8) in refluxing xylene afforded novel trinuclear ruthenium complexes [6-bromopyCHRO]2Ru3(CO)8 (1a-1g) and [6-bromopyC(Me)2O]2Ru3(CO)8 (1h). These complexes were characterized by FT-IR and NMR spectroscopy as well as elemental analysis. The structures of all the complexes were further confirmed by X-ray crystallographic analysis. In the presence of tert-butyl hydroperoxide (TBHP) as the source of oxidant, complexes 1a-1h displayed high catalytic activities for oxidation of primary and secondary alcohols and Most of oxidation reactions could be completed within 1 h at room temperature.